The Relationship Between Interpersonal Communication and Aggressive Behavior Among University Students Actively Involved in Student Organizations at Universitas Negeri Medan - Desi Agustina Br Sembiring; Eva Yulina (Manunggal Halim Jaya, 2026)
Aggressive behavior remains a significant psychological issue among university students, including those actively involved in student organizations. The high intensity of interpersonal interactions, differences in opinions, and complex relational dynamics within student organizations may give rise to interpersonal conflicts that can develop into aggressive behavior. One factor presumed to be associated with aggressive behavior is interpersonal communication. This study aimed to examine the relationship between interpersonal communication and aggressive behavior among university students actively involved in student organizations at Universitas Negeri Medan. A quantitative approach with a correlational research design was employed. The participants consisted of 93 students actively participating in student organizations, selected using purposive sampling. Data were collected using an Interpersonal Communication Scale developed based on DeVito's theory and an adapted version of the Aggression Questionnaire (AQ) developed by Buss and Perry. Data were analyzed using the Pearson Product-Moment correlation test with IBM SPSS Statistics version 26. The results revealed a significant negative relationship between interpersonal communication and aggressive behavior (r = −0.521, p < .001). These findings indicate that students with higher levels of interpersonal communication tend to exhibit lower levels of aggressive behavior, whereas lower interpersonal communication is associated with a greater tendency toward aggressive behavior. The coefficient of determination showed that interpersonal communication accounted for 27.1% of the variance in aggressive behavior. The findings suggest that interpersonal communication is an important relational factor associated with aggressive behavior among students actively involved in student organizations. Therefore, strengthening interpersonal communication skills may serve as an effective strategy for reducing aggressive behavior and fostering healthier and more supportive student organizational environments.